A modular approach to seigniorage in a monetary union. (4th December 2009) - Lange, Carsten; Sauer, Christine
There is little agreement on how to measure seigniorage changes and their sources in a monetary union. This paper informs the debate by developing a modular approach that distinguishes between seigniorage changes a country experiences during the transition phase prior to joining a monetary union and at the time of the regime change when the common currency is introduced. Using the Eurozone enlargement as an example, the underlying components of seigniorage changes for the transition phase and the regime change are identified and quantified. The modular approach thus allows a more informed discussion and provides analysts and policymakers with flexibility as to which seigniorage components to choose depending on the economic issue at hand.